Sekolah Terpadu Di Pekanbaru Dengan Pendekatan Eko Arsitektur - Delvira Desfarisza; Wahyu Hidayat; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Life skills education involves care for the environment can shape the personality and character of skilled care for environment around them. The exixtence of integrated schools thathave continuity from primary level to secondary school, aims to teach character education about care environment through facilities that comply with the national standards of education. A designmethod through applying the principle of eco architecture: (1) Sensitive to the climate; (2) Energyefficient; (3) Eco-friendly, will be applied in buildings such as the use of shading, cross-ventilation,rainwater harvesting, solar panels, and the use of environmentally friendly materials. The concept is applied to the integrated school buildings this is the 'Educational Terrace'. This concept isapplied to the terrace and the veranda building. The terrace and the veranda is utilized as a place of gardening, so with a garden on the terrace can be used to support teaching and learningactivities involves care of the environment.Keywords: Integrated School, Eco Architecture, Educational Terrace.